Review, or reflections on the new economic critique and its horizons - Skomorovskiy, Grigory (Vilnius University Open Series, 2024)
The article is dedicated to reviewing the publication by Polina de Mauny titled Monetary Aspects of the Writer-Publisher Relationship in the Correspondence of Ivan Turgenev and Jules Hetzel (Versus magazine, 2022). De Mauny focused on the economic aspects of the circulation of I. S. Turgenev’s texts in France. Our article provides additional insights into the financial aspects of the literary life in Paris during the second half of the 19th century. These insights are based on analysis of Guy de Maupassant’s correspondence.